Branch surface morphology regulates particulate matter capture in urban trees: implications for exposure risk mitigation across developmental stages - Xiaowu Xu; Guo Liu; Jiahao Zhao; Xinghua Hu; Xizhi Lv (Ecotoxicology and Environmental Safety)
Urban trees contribute to air pollution mitigation; however, the importance of twigs and branches in particulate matter (PM) accumulation has not been sufficiently recognised. In this study, we compared the total PM accumulation mass per unit area on new twigs and perennial branches by partitioning water-insoluble and -soluble fractions. The total PM accumulation of twigs and branches a averaged 63.65 ± 17.90 and 184.17 ± 25.23 μg/cm2 (mean ± SE), respectively. While the soluble PM fractions had similar masses, their proportion was greater in twigs than in branches. Additionally, the morphological traits and elemental composition of superficial PM on twig and branch surfaces were examined in six tree species. PM accumulation was associated with different morphological traits in new twigs, annual branches, perennial branches, and short shoots. The elemental composition of superficial PM on branches indicated geogenic, anthropogenic, and biogenic origins.